The Effect of Coffe Pulp in Ransum to Digestibility In Vivo Etawa Crossbreed Goat (PE) - Beni Lestariono (Fakultas Peternakan, Universitas PGRI Kanjuruhan Malang, 2015)
ABSTRACTThe research was conducted on 9 year July - 7 September 2015 in the village of the District Balesari Ngajum Malang. Analysis of District Proximate is fermented feed at October 20, 2015 held in the Laboratory of Nutrition and FoodCattle Brawijaya University. The method used was in the laboratory experiment and In-Vivo Experiments with using a randomized block design (RAK). Green feed that is given 20% BB. The treatment in this feed is applied, namely PO: 100% pollard. P1: 50% pollard, 50% fermented coffee skin .P2: 40%; 60% pollard skin fermented for coffee flake is followed by LSD test. In the material study using of: Goat PE totaling nine tails, which are grouped based 22kg- 29 kg body weight, feed (forage, leather pollard coffee fermented (KKF).The purpose in the study is to determine of the flake effect fermented coffee using of ration on the digestibility of In-Vivo BK, PK and SK. In this results of this study is expected to be useful as information on the utilization of the fermented coffee flake as alternative feed to improve the digestibility of In-Vivo Etawa Grade Goat (PE). in the fermented of coffee leather waste is the research has great potential as an ingredient substitution Pollard in a goat, because in this results of studies addressing the comparison between Pollard and KKF 50% -50% can improve the digestibility of PK, but it does not make a differences between digestibility BK and SK. Key Words : Etawa crossbreed Goat (PE),Pollard,Skin Coffe Fermented